Constrains on the use of phytoplankton as a biological quality indicator within the Water Framework Directive in portuguese waters - Domingues, Rita B. (2012)
The European Union Water Framework Directive (WFD), a new regulation aiming to achieve and maintain a clean and well-managed water environment, refers to phytoplankton as one of the biological quality elements that should be regularly monitored, and upon which the reference conditions of water quality should be established. However, the use of phytoplankton as a biological quality element will result in several constraints, which are analyzed in this article with examples from Portuguese waters. Specifically, the establishment of reference conditions of water quality may be difficult in some water bodies for which no historical data exists. The sampling frequency proposed for phytoplankton monitoring does not seem suitable to assess phytoplankton succession, and may preclude the detection of algal blooms. Finally, the use of chlorophyll a as a proxy of phytoplankton biomass and abundance has been proposed by some authors, but it may overlook blooms of pico- and small nanophytoplankton, and overestimate the importance of large microphytoplankton. Furthermore, most studies in Portugal have used only inverted microscopy for phytoplankton observation and quantification; this method does not permit the distinction between autotrophic and heterotrophic cells, especially in samples preserved with Lugol’s solution, and does not allow the observation of smaller-sized cells. Finally, some techniques, such as remote sensing and chemotaxonomic analysis, are proposed to be used as supplements in phytoplankton monitoring programs.